A imagem da mulher no cinema da Alemanha Oriental - Alexandre Martins Soares (2017)
After the fall of the Berlin Wall, the films of Deutsche Film AG (DEFA), the State film company of the former German Democratic Republic (GDR), or East Germany, began to be rediscovered by Western researchers. It was verified the existence of the so-called Frauenfilme, or movies about women, also in the East, what was already a film tradition recognized in the production of the New Cinema of the then Federal Republic of Germany (FRG), or West Germany. After German reunification, DEFA disbanded and left behind more than forty years of movie-making feature films, short films, animations and documentaries still poorly researched abroad and virtually unknown in Brazil. Among their sectarian socialist propaganda in audiovisual production, subjected to cultural policy of the Socialist Unity Party of Germany (Sozialistische Einheitspartei Deutschlands-SED), technical and artistic high quality films can be found. Some of these films, especially Frauenfilme, are ambiguous, as it sought to legitimize the SED regime at the same time that made veiled criticism to him. Scholars point to the DEFA as part of an important tradition of not only German cinema and the former Soviet bloc, as well as the world cinematographic History. We intend to show in this thesis (The Image of the Woman in the Cinema of East Germany), that an important part of the former East German State company feacture fiction films is articulated by stories of feminine individuality.